Check-dams as monitoring windows for ecological collapse and microplastic trapping: diatom bioassessment and sediment-core evidence from the Cooum River basin - Sagaya John Paul Joseph; Manjupriya Ayyanar; Lakshmi Priyaa Marimuthu; Sathish Kumar Boopathi; Parvana Chengolikkandi; Subramani Nagaraj (Environmental Monitoring and Assessment, 2026)

Dictyopteris delicatula extract-based bio-coating: a sustainable strategy for extending postharvest shelf life in Climacteric fruits - Sathish Kumar Boopathi; Srioviya Jayabalan; Sagaya John Paul Joseph; Antony Prakash Rejoy Patrick; Arunkumar Kulanthaiyesu; Nagaraj Subramani (Sustainable Chemistry and Pharmacy, 2026)

Ecological dynamics and biodegradation potential of freshwater epiplastic microalgae: A sustainable solution for plastic waste management - Sagaya John Paul Joseph; Jayashree K; Sathish Kumar Boopathi; Antony Prakash Rejoy P; Poornima S; Nagaraj Subramani (Journal of Water Process Engineering, 2025)

Association Between Exposure to Benzophenones and Dietary Pattern and Health Risk Among the General Population in Taiwan - Boopathi Subramani; Yu-Fang Huang; Fang-Chi Chang; Wen-Harn Pan; Mei-Lien Chen (Exposure and Health, 2025)
Benzophenone (BP) and its derivatives are extensively used as UV filters in numerous consumer goods, raising significant concern regarding their potential health risks and environmental contamination. This study sought to evaluate the urinary concentrations of BPs within the general Taiwanese population, investigate the association between internal BP exposure levels and frequency of dietary intake, and assess the resultant health risks. A total of 706 urine samples were obtained from participants in the Nutrition and Health Survey in Taiwan. Quantification of urinary BPs was performed using ultra-high-performance liquid chromatography-tandem mass spectrometry. The median concentrations observed were 2.72 µg/g creatinine (cre.) for BP, 15.17 µg/g cre. for BP-1, and 16.17 µg/g cre. for BP-3, respectively. Adults aged 19–64 years exhibited the highest BP levels and detection frequencies. Statistically significant positive correlations emerged between BP levels and intake of grains, bread, and dairy products within the 19–64 years group adults. In contrast, among children aged 6–11 years, higher BP concentrations were notably linked to meat consumption. Health risk assessment, based on estimated daily BP intake levels, indicated that BP exposure across all age groups remained substantially below the European Food Safety Authority (EFSA) established reference dose of 30 μg/kg-bw/day, thereby indicating a low likelihood of adverse health effects. Nonetheless, further investigation is warranted to elucidate additional exposure sources contributing to BPs exposure.

Piperazine derivatives and bioactive compounds from red seaweed Haloplegma duperreyi: A novel source for inhibition of HIV-I - Sathish Kumar Boopathi; Nagaraj Subramani; Luke Elizabeth Hanna; Lucia Precilla Karunakaran; Sagaya John Paul Joseph; Kotteswari Murugesan (Algal Research, 2025)

The Association of Bisphenol A and Parabens Exposure and Oxidative Stress in Attention-Deficit/Hyperactivity Disorder in Children and Adolescents - Boopathi Subramani; Chia-Huang Chang; Ting-Yu Fang; Ching-Jung Yu; Jung-Chieh Du; Hsien-Chih Chiou; Jia-Woei Hou; Winnie Yang; Hsin-Chang Chen; Ying-Sheue Chen; Betau Hwang; Mei-Lien Chen (Exposure and Health, 2024)

Epiphytic phytoplankton in response to divergent air pollutants from urban and commercial zones of Chennai District, Tamil Nadu, India: A case study towards phytoplankton based Air Quality Index - Sagaya John Paul Joseph; Sreekala Kannikulathel Gopidas; Gomathi Gnanam; Sathish Kumar Boopathi; Nagaraj Subramani (Environmental Science and Pollution Research, 2022)